Metabolite Profiling of the Social Spider Stegodyphus dumicola Along a Climate Gradient - Sandfeld, Tobias; Malmos, Kirsten Gade; Nielsen, Camilla Bak; Lund, Marie Braad; Aagaard, Anne; Bechsgaard, Jesper; Wurster, Martina; Lalk, Michael; Johannsen, Mogens; Vosegaard, Thomas; Bilde, Trine; Schramm, Andreas (Frontiers in Ecology and Evolution, 2022)
Animals experience climatic variation in their natural habitats, which may lead to variation in phenotypic responses among populations through local adaptation or phenotypic plasticity. In ectotherm arthropods, the expression of thermoprotective metabolites such as free amino acids, sugars, and polyols, in response to temperature stress, may facilitate temperature tolerance by regulating cellular homeostasis. If populations experience differences in temperatures, individuals may exhibit population-specific metabolite profiles through differential accumulation of metabolites that facilitate thermal tolerance. Such thermoprotective metabolites may originate from the animals themselves or from their associated microbiome, and hence microbial symbionts may contribute to shape the thermal niche of their host. The social spider Stegodyphus dumicola has extremely low genetic diversity, yet it occupies a relatively broad temperature range occurring across multiple climate zones in Southern Africa. We investigated whether the metabolome, including thermoprotective metabolites, differs between populations, and whether population genetic structure or the spider microbiome may explain potential differences. To address these questions, we assessed metabolite profiles, phylogenetic relationships, and microbiomes in three natural populations along a temperature gradient. The spider microbiomes in three genetically distinct populations of S. dumicola showed no significant population-specific pattern, and none of its dominating genera (Borrelia, Diplorickettsia, and Mycoplasma) are known to facilitate thermal tolerance in hosts. These results do not support a role of the microbiome in shaping the thermal niche of S. dumicola. Metabolite profiles of the three spider populations were significantly different. The variation was driven by multiple metabolites that can be linked to temperature stress (e.g. lactate, succinate or xanthine) and thermal tolerance (e.g. polyols, trehalose, or glycerol): these metabolites had higher relative abundance in spiders from the hottest geographic region. These distinct metabolite profiles are consistent with a potential role of the metabolome in temperature response.